La estructura y el contenido del derecho a la educación como derecho fundamental de defensa y prestación - Scioscioli, Sebastián (2017)
The concept and structure of the right to education as a fundamental right implies the recognition of enforceable legal positions, which can be studied as positive and negative rights. In this paper we investigate the scope and enforcement of the right to education contents according to Argentinian constitutions norms and through the reconstruction of the contents of the States obligations to respect, protect, enforce and guarantee the right.